Philosophical Foundations of Quality of Life : The Selected Works of Alex C. Michalos - Michalos, Alex C. (Springer International Publishing : Imprint: Springer, 2017)
This first volume has as its main focus the philosophical foundations of Michalos' work and describes it in the broad context of the study of logic, the philosophy of social sciences, and a general theory of value. After distinguishing things that have value from the value that things might have, it describes the foundations of a pragmatic theory of value. This theory plays a key role in the author's research on the quality of life and connects his empirical research to the philosophical tradition of the American pragmatists William James, Ralph Barton Perry, John Dewey and Clarence Irving Lewis. The volume addresses various aspects and issues concerning decision making, including decision procedures used in committees, used for assessing the acceptability of scientific theories and new technologies, procedures for a science court, ethical issues involved in the formation of beliefs, some limitations of classical economists' alleged postulates of rational preference, and the importance of analytic guides to decision making. Finally, it describes the organization of the Social Sciences Federation of Canada and a formal accounting system for scientific research.
Keywords: Social sciences.; Logic.; Philosophy and social sciences.; Medical research.; Quality of life.; elektronické knihy; electronic books